2021
DOI: 10.1002/jhbp.895
|View full text |Cite
|
Sign up to set email alerts
|

Serum pancreatic enzymes in the early postoperative period predict complications associated with pancreatic fluid after pancreas transplantation: A retrospective, single‐center, observational cohort study

Abstract: Background Pancreas transplantation (PT) is a radical treatment for diabetes mellitus (DM). Although the results of PT have been improving, surgical complications remain. Few reports have focused on complications associated with pancreatic fluid (CAPF) after PT. We aimed to investigate the risk factors and predictors for CAPF after PT. Methods Sixty‐nine patients, who underwent deceased‐donor PT for type 1 DM at our institution from August 2001 to May 2020, were retrospectively studied. We identified CAPF from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Patients with serum amylase levels ≥75.50 U/L had significantly higher risks of POPF Grade C (RR: 9.87; 95% CI: 1. 19 Increased serum amylase levels have been proven to be a very good predictor of the development of pancreatic fistula after pancreaticoduodenctomy [20][21][22][23][24]. Our results are similar to these ones.…”
Section: Discussionsupporting
confidence: 87%
“…Patients with serum amylase levels ≥75.50 U/L had significantly higher risks of POPF Grade C (RR: 9.87; 95% CI: 1. 19 Increased serum amylase levels have been proven to be a very good predictor of the development of pancreatic fistula after pancreaticoduodenctomy [20][21][22][23][24]. Our results are similar to these ones.…”
Section: Discussionsupporting
confidence: 87%
“…As noted previously by our group, hyperamylasemia after SPK on postoperative day 1 is a significant risk factor for subsequent morbidity [5]. This finding has been reproduced recently by another study [12], and recent findings have also demonstrated hyperamylasemia and postoperative pancreatitis to have clinical relevance after pancreatic resections [13,14]. Thus, drugs targeting pancreatic exocrine suppression-such as somatostatin-analogues-may offer a potential mitigation strategy for pancreas graft related complications after pancreas transplantation.…”
Section: Introductionsupporting
confidence: 80%
“…As no control group was available, it is difficult to assess the exocrine suppressive effect of these somatostatins. As noted in previous studies [ 5 , 12 ], early hyperamylasemia is a significant risk factor for subsequent morbidity after SPK, and interventions mitigating it—such as somatostatin-analogues—could be of interest [ 5 ]. Interestingly, c-peptide levels were significantly lower throughout the first 7 POD’s in the pasireotide group but leveled off during the 180-day follow up, and did not seem to associate with adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study among SPK recipients suggested that elevated plasma amylase levels on postoperative day 1 were significantly correlated with increased incidence of pancreas graft-related complications, need for relaparotomy, and subsequent morbidity 20 . Finally, Tomihara et al 21 presented findings in a small cohort of 69 recipients suggesting an early rise in pancreatic enzymes and some of the complications that were previously reported. Taken together, these studies suggest a possible link between increased perioperative amylase levels and postoperative complications.…”
Section: Discussionmentioning
confidence: 87%
“…Taken together, these studies suggest a possible link between increased perioperative amylase levels and postoperative complications. However, the majority of these studies involved small cohorts, 17 evaluated only one enzyme (amylase), 17,20,22 evaluated only one complication type, 17,21 or only evaluated SPK transplants. 20 Thus, a more comprehensive evaluation of the association of perioperative enzyme elevations and outcomes was undertaken.…”
Section: Discussionmentioning
confidence: 99%